The relationship between physical activity and sleep among adolescents - María Henley Olsen 1999- (2022)
Sleep is important for a healthy development in life. It has also been shown that physical activity has various positive effects on health. It has been proven that physical activity can have healthy benefits in terms of sleep duration. The recommended amount of sleep for adolescents aged from 13-18 years old is 8-10 hours per night. The aim of this study was to survey sleeping habits of adolescents in Iceland and how much physical activity they do, whether this is connected and then how. The hypothesis for the study was that physical activity has an impact on sleeping duration among adolescents. The data was collected from a study conducted by the Icelandic Center for Social Research and Analysis (ICSRA) in 2018. There were 2174 participants in this study and they aged from 15-20 years old and were all students in high schools in Iceland. The participants answered a 92-question questionnaire about their health, sleep, and physical activity. The sleep variable was cross tabulated with, first, how many days per week the participants would engage in physical activity and then again with how many days per week they would engage in physical activity for 60 minutes or longer. The results showed significance (p = 0,01), which suggests that the more often you train per week the more likely it is you sleep the recommended hours per night. Keywords: Sleep, Physical activity, Questionnaire Svefn er talinn vera mikilvægur þáttur fyrir einstaklinginn til að þróa með sér heilbrigt líf. Rannsóknir hafa sýnt fram á að hreyfing hefur jákvæð áhrif á lengd svefns einstaklinga. Ráðlögð lengd svefns fyrir ungmenni á aldrinum 13-18 ára eru 8-10 tímar á hverri nóttu. Markmið þessarar greiningar er að meta hvort íslensk ungmenni hreyfi sig reglulega og hversu mikinn svefn þau fá og jafnframt að meta hvort einhver tengsl séu þarna á milli. Við greininguna var stuðst við fyrirliggjandi gögn frá Rannsóknum og greiningu frá árinu 2018. Þátttakendur könnunarinnar árið 2018 voru á aldrinum 15-20 ára og voru allir nemendur í framhaldsskólum ...